Shell-crossing in quasi-one-dimensional flow - Rampf, Cornelius; Frisch, Uriel (Monthly notices of the Royal Astronomical Society, 2017)
Abstract: Blow-up of solutions for the cosmological fluid equations, often dubbed shell-crossing or orbit crossing, denotes the breakdown of the single-stream